Trigonometric Recurrence and its Limit!

Geometry Level 5

x n + 1 = ( 2 + cos ( 2 α ) ) x n + cos 2 ( α ) ( 2 2 cos ( 2 α ) ) x n + 2 cos ( 2 α ) \large{ x_{n+1} = \dfrac{(2 + \cos(2\alpha))x_n + \cos^2(\alpha)}{(2 - 2\cos(2\alpha))x_n + 2 - \cos(2\alpha)} }

Consider the sequence of real numbers ( x n ) n = 1 (x_n)_{n=1}^\infty defined as above with x 1 = 1 x_1 = 1 for every n N n \in \mathbb N , where α \alpha is a real parameter.

n N \forall \, n \in \mathbb N , let y n = k = 1 n 1 2 x k + 1 \large{y_n = \displaystyle \sum_{k=1}^n \dfrac{1}{2x_k +1}}

For specific values of α \alpha , if the sequence ( y n ) n = 1 (y_n)_{n=1}^\infty has a finite limit, find that limit.

Bonus: Determine the values of α \alpha for which the sequence ( y n ) n = 1 (y_n)_{n=1}^\infty has a finite limit.


The answer is 0.500.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Note that x n > 0 x_n>0 for all n n . We have:

2 x n + 1 + 1 = ( 4 + 2 cos 2 α + 2 2 cos 2 α ) x n + 2 cos 2 α + 2 cos 2 α ( 2 2 cos 2 α ) x n + 2 cos 2 α 2x_{n+1}+1=\dfrac{(4+2\cos2\alpha+2-2\cos2\alpha)x_n+2\cos^2\alpha+2-\cos2\alpha}{(2-2\cos2\alpha)x_n+2-\cos2\alpha}

= 3 ( 2 x n + 1 ) ( 2 2 cos 2 α ) x n + 2 cos 2 α \qquad\qquad\;\,=\dfrac{3(2x_n+1)}{(2-2\cos2\alpha)x_n+2-\cos2\alpha}

which leads to

1 2 x n + 1 + 1 = ( 1 cos 2 α ) ( 2 x n + 1 ) + 1 3 ( 2 x n + 1 ) = 1 3 ( 2 sin 2 α + 1 2 x n + 1 ) \dfrac{1}{2x_{n+1}+1}=\dfrac{(1-\cos2\alpha)(2x_n+1)+1}{3(2x_n+1)}=\dfrac{1}{3}\left(2\sin^2\alpha+\dfrac{1}{2x_n+1}\right) .

This show that: 1 2 x n + 1 + 1 sin 2 α = 1 3 ( 1 2 x n + 1 sin 2 α ) \dfrac{1}{2x_{n+1}+1}-\sin^2\alpha=\dfrac{1}{3}\left(\dfrac{1}{2x_n+1}-\sin^2\alpha\right) ,

Or z n + 1 = 1 3 z n z_{n+1}=\dfrac{1}{3}z_n , where z n = 1 2 x n + 1 sin 2 α z_n=\dfrac{1}{2x_n+1}-\sin^2\alpha .

Thus ( z n ) (z_n) is a geometric progression with z 1 = 1 3 sin 2 α z_1=\dfrac{1}{3}-\sin^2\alpha and ratio q = 1 3 q=\dfrac{1}{3} . Then

k = 1 n z k = ( 1 3 sin 2 α ) 1 1 3 n 1 1 3 = 1 2 ( 1 3 sin 2 α ) ( 1 1 3 n ) \displaystyle \sum_{k=1}^n z_k=\left(\dfrac{1}{3}-\sin^2\alpha\right)\dfrac{1-\dfrac{1}{3^n}}{1-\dfrac{1}{3}}=\dfrac{1}{2}\left(1-3\sin^2\alpha\right)\left(1-\dfrac{1}{3^n}\right)

Thus, y n = k = 1 n ( z k + sin 2 α ) = 1 2 ( 1 3 sin 2 α ) + n sin 2 α \displaystyle y_n=\sum_{k=1}^n(z_k+\sin^2\alpha)=\dfrac{1}{2}\left(1-3\sin^2\alpha\right)+n\sin^2\alpha .

Since the sequence ( 1 3 n ) \left(\dfrac{1}{3^n}\right) converges, the sequence ( y n ) (y_n) converges if and only if the sequence n sin 2 α n\sin^2\alpha converges, or s i n 2 α = 0 sin^2\alpha=0 , that is α = k π , k Z \alpha=k\pi,\; k\in\mathbb{Z} .

Hence, lim n y n = lim n 1 2 ( 1 1 3 n ) = 1 2 \displaystyle\mathop{\lim}\limits_{n\to\infty}y_n=\mathop{\lim}\limits_{n\to\infty}\dfrac{1}{2}\left(1-\dfrac{1}{3^n}\right)=\boxed{\dfrac{1}{2}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...